Evidence‐based prevention of work‐related musculoskeletal injuries in construction industry - Rwamamara, Romuald A.; Lagerqvist, Ove; Olofsson, Thomas; Johansson, Bo M.; Kaminskas, Kazys Algirdas (Journal of Civil Engineering and Management, 2010)
Many construction work tasks are physically very strenuous and the incidence of work‐related musculoskeletal disorders (WMSDs) among construction workers is considerably higher than those in most other occupations. The aim of the study presented in this paper was to contribute to understanding a healthy construction site brought about by the best practices implemented by large construction sites to prevent WMSDs. A triangulation method made of interviews, site observations and studies on company’s documents was used to identify the best practices in 13 several construction projects. A range of the best practices both in the pre‐construction and construction phases of the projects were identified in six different areas of the balance of the construction workplace system; however, there seems to be a significant need for good practices in the management of a systematic work environment. It is now established that Swedish construction industry has several best practices to protect work‐related musculoskeletal health. However, inadequate worker participation and the neglect of health and safety issues by designers in the planning process as well as the implications of some remuneration methods on the production schedule were perceived as detrimental to the musculoskeletal health of construction workers. First Published Online: 10 Feb 2011